From political science to politicizing science? A study of the discipline’s presence in the debates of the United States Congress”, 1981-2021 - Kronlund Anna (Taylor & Francis, 2025)
This article examines how politicians consider political science and political scientists in the United States and more specifically in the United States Congress. The main idea is to examine Congressional debates in the specific timeline starting from the 1980s with an explicit focus on the argumentation of members of Congress. The interest lies in examining how the members include references to political science or political theory in the debates and to what extent the scholars and their works are cited in the debates. The article contributes to the discussions of political science as a discipline in the United States. Furthermore, it examines how the relationship between political science and politics is not only understood but also defined in the political debates of the United States. The article aims to shed light on how politicians are invoking political science and scholars in plenary session debates in contrast to employing expert statements in committee hearings or in the process of drafting bills and other governmental policies.
Keywords: US Congress, debates, political science, political theory, discipline